Effect of Total, Northern and Southern Hemisphere Sunspot Number (Ri, Rn and Rs) on F2- Layer Critical Frequencies at Mid- Latitude Rome Station During the Descending Phase of Solar Cycle 23 - A. Mohammed, Fahmi. (Iraqi Journal of Science, 2023)
The relationship between F2- layer critical frequencies (foF2), total sunspot number (Ri), northern hemisphere sunspot number (Rn) and southern hemisphere sunspot number (Rs) at station located in mid- latitudes on latitude near to latitude of Iraq (Rome station, lat.: 42o N and lon.: 13o E) and for 2003(the descending phase of solar cycle 23) were studied.This research work aims to know the correlation range between them, through correlation coefficients which correlate between them, and hence, the dependence on that index for predicting F2- layer critical frequencies. When the correlation coefficients between foF2, Ri, Rn and Rs were compared for different seasons of 2003, It is found that, correlation coefficient between foF2 and Ri is higher in Winter and Summer than it between foF2, Rn and foF2, Rs in Winter and Summer, too. While, correlation coefficient between foF2 and Rn is higher in Spring and Autumn than it between foF2, Ri and foF2, Rs in Spring and Autumn, too. Also, it is found that, the correlation coefficients between foF2, Ri and foF2, Rn and foF2, Rs were so small that foF2 values are approximately constant as Ri, Rn and Rs values increased, in Autumn.